Gambaran Fungsi Hormon Tiroid Pada Penderita DM Tipe 2 Rawat Jalan - Mardianto Mardianto; Suherdy Suherdy; Dharma Lindarto (Universitas Syiah Kuala, 2010)
AbstractBackground: In previous studies reported that impaired of thyroid function in patients with type 2 diabetes showed different results. This study aims to know the description of the thyroid hormone function in type 2 diabetes mellitus outpatient.Methods: A cross sectional study was conducted from ·September 2009 - March 2010 in H. Adam Malik General Hospital. The subjects were all outpatients at the clinic of Endocrine and Metabolic who met the criteria participated in this study. All samples were examined of TSHs, FT4, adrandom blood glucose, Total cholesterol, HDL cholesterol, and LDL cholesterol.Results: There were 40 patients with type 2 diabetes who had participated in study with 19 men(47.5%), and 21 women (52.5%) with mean age of 58.3 years. We found thyroid dysfunction is10% or 4 people and in details, 2 people (5%) of subclinical hypothyroidism and 2 people 5%) ofsubclinical hyperthyroidism. There were significant differences in average concentrations of three TSHs groups (pl = 0.0010, p2 = 0.012, p3 = 0.001), whereas Fr4 significantly different in eutiroid group and subclinical hyperthyroidism (p2 = 0.00 l) and subclinical hypothyroidism ·group and subclinical hyperthyroidism p3 = 0.001). TSHs levels correlated positively and statisticallysignificant with total cholesterol (r = 0.989, p = 0,011)Conclusions: Overview of thyroid hormone function in 40 patients with type 2 diabetes mellitusindicates 10% of dysfunction with more women than men, and ages who have been affected is over 60 years.(JKS 2010; I: 1-8) Keywords: Dysfunction of Thyroid Hormone, Diabetes Mellitus Type 2",